ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN LMS BERBASIS ARTICULATE STORYLINE PADA PPG PRAJAB - Yudi Pratama; Bayu Kurniawan; Moch. Nurfahrul Lukmanul Khakim; Listyo Yudha Irawan (Raudhah - Proud To Be Professional, 2024)
This research is aimed at analyzing how the learning media needs of PPG Students of IPS State University of Malang are to the content of LMS based on articulate storyline. The research method uses quantitative descriptives using the angket that has been filled by the graduates of the PPG University of Malaang State University IPS prajab wave II of 2024 of 30 students, the results of the Angket are then analyzed and described in order to obtain desired data about media needs learning media. The result of this survey is that the results of this research show that the students of PPG prajab IPS State University Malang have a significant need for interactive, dynamic, and easily accessible learning media in the teaching learning process. Articulate Storyline-based LMS content was rated highly effective in meeting this need, with a majority of respondents stating that the media facilitates deeper material understanding, increases learning motivation, and allows for more flexible learning. The findings underline the importance of further development and integration of Articulate Storyline into LMS as a means of supporting the success of teacher education by providing a more engaging and adaptive learning experience to student needs. The recommendations of this research encourage the use of innovative technology in learning media design to create a more effective learning environment and support the achievement of student competence